An Examination of the Principal Teachings of the Ahmadiyya Community - Nurul Islamiyah; Indo Santalia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study discusses the main teachings of the Ahmadiyah, with the aim of: 1) understanding the history of the emergence of the Ahmadiyah teachings; 2) understanding the main teachings and thoughts of the Ahmadiyah teachings; 3) understanding the differences between the Ahmadiyah teachings and Sunni and Shia teachings. The research method used is library research. The data sources used for this research are books, journals, and websites relevant to the chosen topic. Documentation, specifically searching for notes, books, papers, articles, journals, and other similar sources as research variables, is the method used to collect data.